A PROPHETIC CHURCH IN A MCDONALDIZED SOCIETY - Sanchez, Rene Sanchez (Asian Horizons, 2015)
Vatican II calls forth the “scrutinizing of the signs of the times and interpreting them in the light of the Gospel.” In view of this call, this paper scrutinizes a social phenomenon called the McDonalidized society and asks the pressing question of what it means to be a prophetic church in this society. The paper is divided into three parts. The first part uses the work of the sociologist George Ritzer who analyzes this social phenomenon and its four dimensions of efficiency, calculability, predictability, and control. The second part critically reflects on how this phenomenon creates a human condition of numbness and inauthenticity and its deleterious effects on persons and communities. And the third part presents how the church can be prophetic church in this McDonaldized society. It draws from the concept of “dangerous memories” of Johann Baptist Metz and the concept of “prophetic pathos” of Walter Bruggemann as theological paradigms in understanding how the church as a prophetic church can confront this pervasive numbness and inauthenticity and offer an alternative way of being human. The significance of this paper is its concrete way of showing how the call of Vatican II can be concretely pursued by the church’s engagement with contemporary society with its prophetic vision and hope.